Extreme Hypofractionation with SBRT in Localized Prostate Cancer. - Antonia Gómez-Aparicio, Maria; Valero, Jeannette; Caballero, Begoña; García, Rafael; Hernando-Requejo, Ovidio; Montero, Ángel; Gómez-Iturriaga, Alfonso; Zilli, Thomas; Ost, Piet; López-Campos, Fernando; Couñago, Felipe (Current Oncology, 2021)
Prostate cancer is the most commonly diagnosed cancer among men around the world. Radiotherapy is a standard of care treatment option for men with localized prostate cancer. Over the years, radiation delivery modalities have contributed to increased precision of treatment, employing radiobiological insights to shorten the overall treatment time, improving the control of the disease without increasing toxicities. Stereotactic body radiation therapy (SBRT) represents an extreme form of hypofractionated radiotherapy in which treatment is usually delivered in 1-5 fractions. This review assesses the main efficacy and toxicity data of SBRT in non-metastatic prostate cancer and discusses the potential to implement this scheme in routine clinical practice.